L'Inferno e Ugone d'Alvernia: analisi morfologica di un testo cavalleresco e analisi comparativa di Alcuni inferni. - Van Heerden, Helga Dieta. (My University, 1987)
This thesis examines a medieval text which forms part of Italian chevalric literature i.e. The story of Ugone d'Alvernia. Its original name was Huon d'Auvergne. Firstly the text will be examined from the historic angle and then from a more scientific point of view. It shows how the original "chanson de geste", written in French was brought by the French "jongleurs" into Italy and became initialized, producing a unique phenomenon, a linguistic mixture known as franco-venetian. This literature played a decisive part in the diffusion of the stories surrounding Charlemagne. Huon d'Auvergne was elaborated and extended by Andrea da Barberino (c. 1370-1432) and called La Storia di Ugone d' Alvernia (The story of Ugone Of Alvernia). Various descents into Hell are then examined , from both the classic and the Christian point of view. This examination leads on to the comparison of the two "Inferni" described by Andrea da Barberino in his two works La Storia di Ugone d' Alvernia and in Guerino il Meschino with the descent described by Dante in his Inferno. A morphological analysis of the text is then undertaken. It applies the theory propounded and used by Propp in his morphological analysis of some Russian fairy tales. According to the theory there are thirty-one "functions" which can be applied in such an analysis
A Dissertation submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, for the degree of master of Arts.
Keywords: Epic poetry, Italian -- History and criticism.; Huon D'Auvergne (Chanson De Geste); Chansons de geste -- History and criticism.; Hell in literature.